2020
DOI: 10.1111/jvh.13456
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for chronic hepatitis E virus infection: A systematic review and meta‐analysis

Abstract: Hepatitis E virus infection can cause chronic hepatitis in immunocompromised patients with significant chance of progressive fibrosis and possibly cirrhosis. The aim of this systematic review was to summarize the efficacy and safety of the various treatment options for chronic hepatitis E. We performed a systematic literature search. The primary outcome measure was a sustained virological response (SVR). Secondary end points were rapid virological response (RVR), relapse rates, side effects and adverse events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 89 publications
0
38
0
Order By: Relevance
“…No median dose was calculated but the range was 29-1200 mg/day. 16 It was also reported that 52% patients required a dose reduction due to anaemia. These studies have a median treatment length of 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No median dose was calculated but the range was 29-1200 mg/day. 16 It was also reported that 52% patients required a dose reduction due to anaemia. These studies have a median treatment length of 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…A meta‐analysis published in 2020 reviewed 582 patients who received treatment with ribavirin for chronic hepatitis E. The SVR rate was 76%, and again, the median duration of treatment was 3 months (range 0.3–32). No median dose was calculated but the range was 29–1200 mg/day 16 . It was also reported that 52% patients required a dose reduction due to anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…This bears important biological and therapeutic implications, as inhibiting basal interferon activation by JAK inhibitor further promoted HEV replication, whereas therapeutic treatment with recombinant IFNα inhibited viral replication. PEGylated IFNα has been administered to a small number of chronic HEV patients with about 85% response rate, but this treatment has a high risk of causing acute transplant rejection ( 47 ). HEV replication in cell lines has been shown to barely activate type I but mildly type III interferon response ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…If modification of the immunosuppressant regimen is not possible or is unsuccessful, pharmacological agents such as ribavirin and/or pegylated interferon-alpha (peg-IFN) can be used[ 171 ]. In a meta-analysis that included 395 patients with chronic hepatitis E, ribavirin monotherapy for a median of 3 mo achieved sustained virological response (SVR) in 76% of patients[ 172 ]. The reported dose of ribavirin in the literature ranged from 29 to 1200 mg/d, and the duration from 1 to 18 mo.…”
Section: Treatmentmentioning
confidence: 99%
“…HEV RNA should be assessed in the serum and in the stool before treatment discontinuation[ 169 ]. A second course of ribavirin for 6 mo can be attempted in cases of treatment failure[ 172 ]. HEV RNA concentrations decrease within the first week of initiating ribavirin therapy, and a greater reduction in viral load on day 7 is an independent predictor of SVR[ 174 ].…”
Section: Treatmentmentioning
confidence: 99%